Oral cyclophosphamide without corticosteroids to treat mucous membrane pemphigoid. (30th January 2013) - Munyangango, E.M.; Le Roux‐Villet, C.; Doan, S.; Pascal, F.; Soued, I.; Alexandre, M.; Heller, M.; Lièvre, N.; Aucouturier, F.; Caux, F.; Laroche, L.; Prost‐Squarcioni, C.
Summary Background Mucous membrane pemphigoid (MMP) still represents a potentially life‐ and sight‐threatening disease. Immunosuppressants, such as cyclophosphamide (CYC), are indicated for patients with severe and/or refractory MMP. Objectives To evaluate the efficacy and safety of daily oral CYC without corticosteroids as therapy for severe MMP. Methods Thirteen patients with severe refractory MMP, who received oral CYC at an initial dose of 2 mg kg−1 without corticosteroids, were retained. Previous treatments, for example dapsone, sulfasalazine or topical agents, were maintained during CYC treatment. Initial clinical severity and response to treatment were assessed by scoring. CYC was stopped after complete remission (CR), or when MMP progressed or lymphopenia (< 0·7 × 109 cells L−1) occurred. Results After 52 weeks of CYC treatment, the overall response rate was 69% (9/13 patients) with a median time to disease control of 8 weeks (range 4–52 weeks). Seven patients (54%) entered CR with a median time to CR of 24 weeks (range 16–52 weeks), all remaining in CR at week 52. The mean duration of CYC administration was 12 weeks (range 2–52 weeks). The most common side effect was lymphopenia (10/13 patients), which led to CYC withdrawal for six patients. No sepsis was observed. Conclusions CYC without corticosteroids had rapid efficacy in patients with severe refractory MMP and was safe.